Comparative Studies on the pH Dependence of DOW of Microcystin-RR and -LR Using LC-MS - Gaodao Liang; Ping Xie; Jun Chen; Ting Yu (The Scientific World Journal)
Microcystins (MCs) are well known worldwide as hepatotoxins produced by cyanobacteria, but little is known about the physicochemical properties of these compounds. The dependence of the n-octanol/water distribution ratio (DOW) of MC-RR and -LR to pH was measured by high-performance liquid chromatography combined with mass spectrometry (LC-MS). There was a remarkable difference in such relationships between MC-RR and -LR. The log DOW of MC-LR decreased from 1.63 at pH 1.0 to -1.26 at pH 6.5, and stabilized between -1.04 and -1.56 at a pH of 6.5~12.0; log DOW of MC-RR varied between -1.24 and -0.67 at a pH of 1.00~4.00, and stabilized between -1.20 and -1.54 at a pH of 4.00~12.00. The difference of hydrophobicity in acidic condition between MC-RR and -LR is important, not only for the analytical method of both toxins, but perhaps also for understanding the difference of toxicity to animals between the two toxins.